Patients with dengue clinical-epidemiological behavior. Comparative study of two case series - Carlos A. García Gómez; Samuel Sánchez Sánchez; Dagmara Pantoja Fonseca; Osvaldo Rodríguez Morales; Ana Laura Navarro Baldellot; Carlos García Mantecón (Medisur)
Background: The disease caused by the dengue virus constitutes a serious health problem for tropical countries. The last decade has seen the re-emergence of this entity in Cuba, with evident changes in its clinical behavior. Objective: to compare the clinical-epidemiological behavior between two series of cases of patients with dengue confirmed diagnosis, in different periods of time. Methods: a descriptive, comparative study that included two series of cases of hospitalized patients with dengue confirmed diagnosis: series A, sample of 83 patients seen in 2017; and series B, sample of 327 seen in 2018. Variables such as: age, signs and symptoms, clinical findings, alarm signs, severe forms, and indicators of quality of care in dengue patients were analyzed. Results: in general, the acute febrile syndrome predominated, although other signs and symptoms such as asthenia, anorexia, rash and retro-ocular pain, manifested a higher incidence in series B. In both groups the most frequent paraclinical finding was lymphocytosis. In series B, the quality standards for the care of patients with dengue were more affected; as well as it also presented a higher rate of alarm signs, serious forms and complications. Conclusions: Although the study analyzed series of patients in two consecutive periods, the more complex behavior was evident in the second, due to the higher incidence of symptoms and less favorable figures for the quality standards established for the disease.